2019
DOI: 10.1007/s00125-018-4807-8
|View full text |Cite
|
Sign up to set email alerts
|

Preserved glucose response to low-dose glucagon after exercise in insulin-pump-treated individuals with type 1 diabetes: a randomised crossover study

Abstract: Aims/hypothesis This study aimed to compare the increase in plasma glucose after a subcutaneous injection of 200 μg glucagon given after 45 min of cycling with resting (study 1) and to investigate the effects of glucagon when injected before compared with after 45 min of cycling (study 2). We hypothesised that: (1) the glucose response to glucagon would be similar after cycling and resting; and (2) giving glucagon before the activity would prevent the exercise-induced fall in blood glucose during exercise and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 35 publications
0
8
0
2
Order By: Relevance
“…A recent outpatient study demonstrated that the plasma glucose response to 150 µg soluble glucagon was comparable to that of 40 g glucose taken as tabs [15]. However, several conditions may impair glucagon’s efficacy, i.e., low carbohydrate diets [16], exercise [17], ethanol intake [18], and hyperinsulinemia [19]. Therefore, if low-dose glucagon should be used in everyday treatment of mild hypoglycemia, a variable dosing regimen depending on these factors may be preferable as shown in a simulation study proposing an insulin-dependent glucagon dosing regimen for treatment of mild hypoglycemia [20].…”
Section: Discussionmentioning
confidence: 99%
“…A recent outpatient study demonstrated that the plasma glucose response to 150 µg soluble glucagon was comparable to that of 40 g glucose taken as tabs [15]. However, several conditions may impair glucagon’s efficacy, i.e., low carbohydrate diets [16], exercise [17], ethanol intake [18], and hyperinsulinemia [19]. Therefore, if low-dose glucagon should be used in everyday treatment of mild hypoglycemia, a variable dosing regimen depending on these factors may be preferable as shown in a simulation study proposing an insulin-dependent glucagon dosing regimen for treatment of mild hypoglycemia [20].…”
Section: Discussionmentioning
confidence: 99%
“…A study by Steineck et al demonstrated that the glucose response to low‐dose glucagon is not impaired after or during 45 min of moderate exercise; conversely, it is enhanced. Additionally, glucagon could be used immediately before starting exercise to minimize the subsequent glucose decline 42,96,97 . However, whether the glucose response to glucagon is preserved after prolonged exercise, with the risk of emptying liver glycogen depots, remains unclear.…”
Section: Potential Limitations Of Regular Glucagon Usementioning
confidence: 99%
“…The inclusion criteria were as follows: age 18-70 years; body mass index 20-30 kg/m 2 ; HbA1c £8.5% (£69 mmol/mol); duration of type 1 diabetes ‡2 years; insulin pump treatment ‡1 year, selfreported hypoglycemia awareness, and use of carbohydrate counting and the insulin pump bolus calculator for all meals. Participants were excluded if unable to stop paracetamol usage during the study period, pregnant or breast-feeding, performing vigorous intense aerobic exercise more than 3 h per week due to a second study performed simultaneously, 5 or using medication besides insulin, influencing glucose metabolism.…”
Section: Recruitmentmentioning
confidence: 99%